A time to trust? The buffering effect of trust and its temporal variations in the context of high‐reliability teams. (23rd February 2018) - Burtscher, Michael J.; Meyer, Bertolt; Jonas, Klaus; Feese, Sebastian; Tröster, Gerhard
Summary: This study aims to further clarify the functionality of job resources in the context of high‐reliability teams. Combining extant stress models with theoretical considerations from team research, we address temporal variations in the buffering effect of trust in teammates. We hypothesize that trust buffers the negative effect of objective physical activity on perceived strain and that this buffering effect is more pronounced during later performance episodes (i.e., when employees complete a series of temporally distinguishable tasks). We tested the hypotheses with a sample of professional firefighters who completed a sequence of 3 performance episodes in a high‐fidelity simulation environment. Each participant was equipped with a smartphone capturing individual motion activity, which we used as an indicator of physical activity. In line with our hypotheses, multilevel modeling revealed a buffering effect of trust on the relationship between physical activity and perceived strain. Importantly, this buffering effect was more pronounced in the second performance episode as compared with the first performance episode. Our findings add a temporal perspective to the understanding of the effectiveness of job resources. In addition, the current study illustrates the usefulness of smartphones for obtaining behavioral data in a naturalistic setting.